What Do We Really Know about the Transatlantic Current Account? - Martin T. Braml; Gabriel J. Felbermayr (Center for Economic Studies and ifo Institute (CESifo), 2019)
Do the U.S. have a current account surplus or a deficit with the EU? Since 2009, official sources disagree: The U.S. Department of Commerce claims a consistent U.S. surplus while Eurostat reports the opposite. International transactions are notoriously difficult to measure accurately, but the size of the transatlantic discrepancy is extremely substantial: over the last ten years, it has grown to a cumulated 1 Trillion USD. In times of severe trade policy disagreements across the Atlantic, this gap is obviously problematic. This paper tries to dissect the transatlantic reporting gap. Two country-pairs – U.S.-UK and U.S.-Netherlands – account for almost the entire transatlantic discrepancy, which, in 2017, stood at about 180 billion USD. In the former case, national statistics on net services trade disagree by as much as 55 billion USD; in the latter case, there is a reporting difference in net primary income of about 60 billion USD. In contrast, data provided by the Bundesbank for the German-U.S. current account closely mirror U.S. data. Non-random measurement error and, possibly, deliberate manipulation seem to cause the observed discrepancies.
Keywords: F14; F32; H26; 330; current account; statistical discrepancies; service trade; trade war